2014
DOI: 10.23986/afsci.8682
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lighting, semi-closed greenhouse and split-root fertigation on energy use and CO2 emissions in high latitude cucumber growing

Abstract: Effects of supplemental lighting, semi-closed greenhouse and split-root fertigation on weekly to seasonal heat and electricity use and CO2 emissions in cucumber growing were estimated in Finland. With moderate lighting (170 W m-2 above rows, 60 W m-2 inter-row) in a ventilated greenhouse, seasonal electricity and heat use (MJ kg-1 cucumber) were 20–50 and 10–25, 17–30 and 3–8, 38–55 and 10–18 in spring, summer and autumn to mid-winter, respectively. In summer, a semi-closed greenhouse improved energy use effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The energy systems of the semi-closed greenhouse include groundwater sources (hot-and cold-water wells), groundwater energy exchange system (high-efficiency plate energy exchanger), heat pump, the end system (greenhouse heating ducts and ATU), and energy storage system (heat storage tank and cold storage tank). The operation manners of energy systems and climate controls can be referenced in De Gelder et al 2012, Gieling et al (2011), and Kaukoranta et al (2014), which mainly depend on energysaving strategies and commercial crop management practices in China.…”
Section: Methodsmentioning
confidence: 99%
“…The energy systems of the semi-closed greenhouse include groundwater sources (hot-and cold-water wells), groundwater energy exchange system (high-efficiency plate energy exchanger), heat pump, the end system (greenhouse heating ducts and ATU), and energy storage system (heat storage tank and cold storage tank). The operation manners of energy systems and climate controls can be referenced in De Gelder et al 2012, Gieling et al (2011), and Kaukoranta et al (2014), which mainly depend on energysaving strategies and commercial crop management practices in China.…”
Section: Methodsmentioning
confidence: 99%
“…For example photo cultures are used in Finland when producing lettuce, cucumbers, and tomatoes. Yearly average power consumption are: heating -11 Mj/kg, lightning -32 Mj/kg [7].…”
Section: A Greenhouse Vegetable Productionmentioning
confidence: 99%
“…In colder climates, winter heating demands are significantly increased and closed greenhouse installations are limited. Experiments in semi‐closed greenhouses with heat recovery ventilation in Finland showed a decrease in the summer heating usage by 35–50%, but no significant reductions throughout the rest of the year . Wong et al .…”
Section: Introductionmentioning
confidence: 99%
“…In colder climates, winter heating demands are significantly increased and closed greenhouse installations are limited. Experiments in semi-closed greenhouses with heat recovery ventilation in Finland showed a decrease in the summer heating usage by 35-50%, but no significant reductions throughout the rest of the year [12]. Wong et al assessed the closed greenhouse with seasonal storage for the Canadian climate setting and found that annual greenhouse gas emissions could be reduced by up to 86% [1].…”
Section: Introductionmentioning
confidence: 99%